Emotional expression in conversations about advance care planning among older adult home health patients and their caregivers. Issue 9 (September 2021) - Tay, Djin L.; Ellington, Lee; Towsley, Gail L.; Supiano, Katherine; Berg, Cynthia A.
Highlights: Patients' and caregivers' emotional expression during an ACP planning intervention was mostly positive. Patients and caregivers were similar in expression and positive and negative valence across topics during ACP discussions. Five out of 18 patient-caregiver dyads (28%) had interactions where emotional expression was avoided. Findings describe emotional contexts during shared decisions and have implications for future research and practice. Abstract: Objectives: To examine patient and caregivers' differences in emotional expression and explore topics associated with emotional expression during advance care planning (ACP) discussions. Methods: Older adult home health patient-caregiver dyads participated in video-recorded ACP conversations as part of a collaboration-focused intervention study. Recordings were coded in Noldus Observer XT, analyzed with descriptive statistics, Cochran-Mantel-Haenszel and Breslow-Day test, and integrated with qualitative content analysis. Results: Eighteen patient-caregiver dyads were purposively recruited. Participants were mostly female (11 patients; 13 caregivers). Mean ages were 68.22 ( SD = 9.64) for patients and 61.28 ( SD = 13.60) for caregivers. Emotional expression (depth of emotion, positive and negative valence) was similar across patients and caregivers. Conversations centered on positive and negative decisional, relational, and existential topics. Conclusions: This study explored emotional expression and identified topics associated with emotion for patients and caregivers during collaborative ACP. Findings suggest that collaboration in ACP can have positive relational aspects for patient-caregiver dyads, while negative emotions can also be distressing. Practice implications: This study describes the range of emotions that are common during patient and caregiver ACP discussions. Clinical implications for the assessment of caregiver support and awareness of the interdependent nature of decision making is discussed.